2020
DOI: 10.3390/nu12082289
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Physical Activity and Ultra-Processed Food Consumption in Adolescents from Different Countries during Covid-19 Pandemic: An Observational Study

Abstract: Aim: to describe physical activity and ultra-processed foods consumption, their changes and sociodemographic predictors among adolescents from countries in Europe (Italy and Spain) and Latin America (Brazil, Chile, and Colombia) during the SARS-CoV-2-pandemic period. Methods: Cross-sectional study via web survey. International Physical Activity Questionnaire (IPAQ) and weekly ultra-processed food consumption data were used. To compare the frequencies of physical activity status with sociodemographic variables,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
220
5
42

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(287 citation statements)
references
References 31 publications
20
220
5
42
Order By: Relevance
“…Of the five studies that measured changes in SB in children and adolescents, three studies 42 62 65 used non-validated questionaries and the remaining two studies 71 82 used validated questionaries. Time spent in SB was reported in 3/5 studies, with the remaining two studies reporting changes in SB as a percentage of their respective populations.…”
Section: Resultsmentioning
confidence: 99%
“…Of the five studies that measured changes in SB in children and adolescents, three studies 42 62 65 used non-validated questionaries and the remaining two studies 71 82 used validated questionaries. Time spent in SB was reported in 3/5 studies, with the remaining two studies reporting changes in SB as a percentage of their respective populations.…”
Section: Resultsmentioning
confidence: 99%
“…Studies carried out in different countries have reported changes in eating habits associated with lockdown regardless of the degree of restrictions imposed. A number of those studies report greater consumption of comfort foods with a high sugar content, such as chocolate and salty snacks [ 35 ], which participants attributed to the state of increased anxiety [ 10 ]. In this study, we identified an Unhealthy snack foods and beverage pattern of change in eating habits that reflects this trend.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies report increased sedentary lifestyle, screen time, and decreased exposure to sunlight as health-related behaviors modified during lockdown in different countries [ 12 , 16 , 17 , 35 , 36 ]. Other research described an increase in inactivity during lockdown among children [ 12 , 33 ] and adolescents [ 35 ] associated with a higher educational level of mothers.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic, disruptions in food supply chains and panic buying (due to lockdown fears) may have limited access to fresh foods, tilting the balance towards a greater consumption of ultraprocessed foods and other foods with long shelf lives, which are usually high in salt, sugar and saturated fat. Two Brazilian studies found this to be more evident in less economically developed regions and in those with less education 25,26 A web survey found that the increase in ultraprocessed food consumption during the pandemic was more pronounced in LA (Brazil, Argentina, Colombia and Chile) than in Europe 27 . In a Chilean survey, the increase in fried food consumption was positively associated with weight gain during confinement 28 …”
Section: Obesity In Lamentioning
confidence: 99%